Pulmonary venous flow pattern--its relationship to cardiac dynamics. A pulsed Doppler echocardiographic study - Keren, G; Sherez, J; Megidish, R; Levitt, B; Laniado, S (Circulation (New York, N.Y.), 1985)
We studied the physiology of pulmonary venous flow in 13 normal subjects and five patients with atrial rhythm disorders and atrioventricular conduction disturbances with pulsed Doppler and two-dimensional echocardiography. The left atrium, mitral valve, and pulmonary venous ostia were visualized through the apical four-chamber view. Mitral and pulmonary venous flows were obtained by placing the Doppler sample volume at the appropriate orifice. Pulmonary venous flow was biphasic: a rapid filling wave was observed during systole when the mitral valve was closed; a second wave was observed in diastole during the rapid ventricular filling phase of mitral flow, but was significantly delayed. In patients without atrial contraction (atrial fibrillation and sinoatrial standstill), the initial rapid filling was greatly diminished and only the second diastolic wave appeared to contribute to left atrial filling. In patients with high-grade atrioventricular block, each atrial contraction was followed by a surge in flow from the pulmonary veins. These results are consistent with data obtained from invasive measurements in both dogs and man, and confirm the validity of the use of pulsed Doppler echocardiography in the study of pulmonary venous flow. We suggest that pulmonary venous flow is influenced by dynamic changes in left atrial pressure created by contraction and relaxation of the atrium and ventricle. The initial peak in pulmonary venous flow occurs with atrial relaxation simultaneously with the reduction of left atrial pressure, and the second peak occurs with left ventricular relaxation and rapid transmitral filling of the ventricle.